Motivational strategies in social english classes for second year mainstream students at faculty of english language teacher education, hanoi university of languages and international studies, vietnam national university (FELTE - HULIS – VNU) = chiến lược tạo động lực học trong giờ học môn tiếng anh xã hội của sinh viên năm hai khoa sư phạm tiếng Anh, Trường Đại học Ngoại ngữ - Đại học quốc gia Hà Nội - Dương, Thị Lê Dung (2020)
In Vietnam, students’ English communication skills are generally weak due to the fact that the traditional method of teaching and learning English focuses on knowledge of language rather than skills. Consequently, students in Vietnam are neither active nor enthusiastic in activities that emphasize communication between participants. Therefore, English teachers need to adapt some changes in their approaches or strategies in teaching, one of which is motivational strategies. In the context of Faculty of English Teacher Education (FELTE), Hanoi University of Languages and International Studies (HULIS), Vietnam National University (VNU), motivational strategies have been applied in Social English classes for students. Therefore, whether teachers efficiently and successfully employ the motivational strategies is taken into consideration and urges the researcher to conduct this study. For the past few years, the teacher’s use of motivational strategies has received increasing attention when a number of studies have been conducted to explore the application of such strategies and their effectiveness. In the context of FELTE, HULIS, VNU, several researchers have made an effort to investigate certain methods used by teacher to pursue motivational strategies in English teaching. However, none of them has touched upon the motivational strategies employed by teachers as perceived by second year students and the researcher’s observation. All of the aforementioned reasons urged the researcher to conduct this research paper aiming at investigating the frequency and effectiveness of the motivational strategies employed by teachers in Social English class of second year students as perceived by students themselves. The paper is a mixed research that adopted both quantitative and qualitative methods to bring together the strengths of both forms of research to compare and validate results. The results of the survey conducted among 120 HULIS sophomores and the observation of five Social English classes revealed that students preferred mostly 3 motivational strategies, which were Personalization (Creating opportunities for students to express personal meanings including experiences, feelings, opinions), Team competition (Using activities which raise competition among groups) and Promoting cooperation (Setting up a cooperative learning activity or encouraging students to help one another, offering suggestion on how best to do this.). The results signified that the current motivational strategies applied received positive reaction from the students and there was a good trend of applying motivational strategies in ULIS. Lastly, the research contributed to the volume of research on motivational strategies as well as serves as a reference material for those who are interested in the same research topics.